Rancang Bangun Simulator Sistem Starter Sepeda Motor Dalam Mengatasi Keterbatasan Media Pembelajaran - Irma Yulia Basri; Delsina Faiza; Remon Lapisa; M. Natsir; Hasan Maksum; Giatman Giatman (Jurnal Pendidikan Teknik Elektro, 2021)
The condition of COVID-19 has changed the living order of all units. The government and the entire community concentrate on the importance of public safety, with the consequence that funds from different units are allocated to COVID-19 disaster management, including the allocation of educational funds. Procurement for SMK education facilities and infrastructure, previously restricted by training facilities, such as a motorcycle auto-study program (TOSM) of SMKN 1 XI Koto Tarusan-Pesisir Selatan, has been affected by changes in funding from the Ministry of Education and Culture. The absence of learning media and the small number of active teachers from TOSM means that the capacity of TOSM students to fulfill the minimum industry requirements, which is shown by only 16% of SMKN 1 XI Koto Tarusan graduates who can be accepted immediately into the world of work. In a workshop on the design of a motorcycle starter device simulator to solve the problem of incomplete learning media, the implementation team helped develop learning media. This activity took place at SMKN 1 XI Koto Tarusan Pesisir Selatan from 25 to 28 September 2020. There were 10 teachers involved in the course. The production for this operation is 2 motorcycle starter system simulators, which can be used in the teaching and learning process as learning media.